The Role of Understanding the Concept of Islamic Wasathiyah in Shaping Inclusive Education Practices in Pondok Pesantren - Abdulah, Achmad Afif; Zaki, Muhammad; Mabruri, Mabruri (At-Tarbiyat, 2024)
This article explains the implementation of the characteristics of wasathiyah Islam in Islamic boarding schools. Islamic boarding schools are one of the existing education systems in Indonesia that teach Islamic characteristics. But lately we have come across groups that are radical Islam who are intolerant. The implementation of wasathiyah Islamic character is important to avoid radical religious thinking and foster an open attitude towards other beliefs. So this article seeks to answer what are the forms of wasathiyah Islamic characteristics that have been implemented in the As-Salam Rimbo Bujang Islamic Boarding School? and what is the form of implementation of wasathiyah Islamic characteristics in the As-Salam Rimbo Bujang Islamic Boarding School? And to answer the question, the researcher conducted a field research with a qualitative approach and in data acquisition was carried out by observation, interviews, and documentation. Then several theories were used to analyze the data from the research. From this research, the final result was obtained that the As-Salam Islamic Boarding School had implemented the characteristics of wasathiyah Islam well. The good implementation of the characteristics of wasathiyah Islam at the As-Salam Rimbo Bujang Islamic Boarding School is a form of the success of the Islamic Boarding School in producing students who respect each other and are highly tolerant. The results of this study will provide insight to the general public that the As-Salam Rimbo Bujang Islamic Boarding School is one of the parts of the Islamic Boarding School that implements the implementation of wasathiyah Islamic characteristics.